Quality of life of displaced persons from fighting under registration of MOI and UNHCR at Mae La Temporary Shelter Thasongyang District, Tak Province. - Suriyos, C.; Kanchanatawan, B. (Chulalongkorn Medical Journal, 2023)
Background : Wars have serious impacts on individual’s mind and body, bringing to Migration from their troubled homeland to another country that is safe and stable can improve quality of life of displaced person from fighting. Objective : To study the quality of life and relating factors of displaced persons from fighting under registration of Memorandum of Understanding (MOI) and United Nations High Commissioner for Refugees (UNHCR) at Mae La Temporary Shelter, Thasongyang District, Tak Province. Design This research is a cross-sectional descriptive study Setting : Mae La Temporary Shelter,Thasongyang District,Tak Province Materials and Methods : Data were collected from 110 displaced persons from fighting, aged 18 - 60 years old. All study population answered 1) personal information questionnaire, and 2) World Health Organization Quality of Life Brief – Thai (WHOQOL-BREF-THAI, via Burmese translation version that was reviewed by language experts in Thailand and Myanmar, validity and reliability assessed resulted Cronbach’s Alpha of 0.88. Results : Results found that displaced persons from fighting have an average overall score of quality of life 83.19. Factors relating to the overall quality of life found that time living in Mae La temporary shelter, sex, helps from other agencies, satisfaction to live in Mae La Temporary Shelter, relationships with neighbors, food and clothing sufficiency significantly statistical differs at p <0.05. Conclusion : The overall quality of life of displaced persons from fighting is in moderate level. Factors related to the overall quality of life are time living at Mae La Temporary Shelter, sex, helps from other agencies, satisfaction to live at Mae La Temporary Shelter, relationships with neighbors, sufficiency of food and clothing.